Clinical Legal Education in the Legal Aid Institution - Ulfah, Maria (Faculty of Law Universitas Negeri Semarang, 2019)
Clinical legal education in a Faculty of Law can be done through the curriculum or ongoing regular activities outside the curriculum. Many campuses have implemented clinical legal education in the compulsory courses or elective courses. It would be good if the clinical legal education has been implemented in the course of one eye, but the setting of clinical legal education in a college course for which has not been set is not easy to do. Difficulty setting of clinical legal education in the subjects did not dampen interest in developing clinical legal education on the campus. Faculty of Law, Universitas Katolik Parahyangan (UNPAR) develop it through ongoing routine activities included in the